Validity and reliability of the Arabic version of knowledge, attitudes, and practices toward COVID-19 preventative behaviors (KAP COVID-19) - Bajamal, Eman; Alanazi, Mona (Frontiers in Public Health, 2023)
Background: Even though the innovation of COVID-19 vaccination effectively protects against the virus, practicing preventative behaviors is still essential. However, public adherence to preventive behaviors relies mainly on the individuals' knowledge, attitudes, and practices (KAP) toward COVID-19 preventative behaviors. Therefore, it is crucial to evaluate these aspects.Nevertheless, there is no validated scale that assesses KAP toward COVID-19 preventative behaviors. To evaluate the psychometric properties of the Arabic version of knowledge, attitudes, and practices toward coronavirus disease 2019 (COVID-19) preventative behaviors.Methods: A quantitative descriptive cross-sectional design was used to develop and evaluate the psychometric properties of KAP through specific stages: item development, face, content, convergent and construct validity evaluation, and internal consistency. Data were collected online through "google forms" from June 2020 to July 2020. Both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to assess the construct validity.Results: A total of 1,363 participants completed the scale. The overall Cronbach's alpha was .83, indicating good internal consistency. Exploratory factor analysis supported structural validity for all the scale items with KMO .78, .60, and .81, respectively, and Bartlett's Test of Sphericity = (p <.05). Convergent validity was confirmed by a moderate correlation between the KAP scale items, knowledge ranging from r = .11 (p < .01) to r = .62 (p < .01), attitude ranging from r = .158 (p < .01) to r = .584 (p < .01), and practice ranging from r = .383 (p < .01) to r = .774 (p < .01).The psychometric properties of the scale indicate that the KAP is a valid and reliable scale that can be utilized to evaluate the level of KAP toward COVID-19 preventative behaviors among the population in Saudi Arabia.